Navigating Between Innovation and Compliance: The Challenges of Sharia Fintech Implementation in Indonesia's Financial Ecosystem - Ine Nurul Lutfiah (Walidem Institute and Publishing (WIP), 2024)
This study aims to investigate the key challenges faced in the implementation of sharia fintech in Indonesia, focusing on navigating between technological innovation and sharia compliance in the financial ecosystem. The research methods used include an in-depth literature review on the latest developments in Sharia fintech, policy analysis, and interviews with stakeholders of the financial and Sharia industry in Indonesia. The results show that despite a great push to introduce fintech innovation in the context of sharia, its implementation is faced with several challenges. These challenges include the need for a clearer regulatory framework, a better understanding of Islamic principles in financial technology, and better integration between Islamic financial institutions and fintech players. In addition, it is also important to overcome the problem of public trust in Islamic financial technology. These findings underscore the complexity and importance of a holistic and collaborative strategy in advancing Islamic fintech in Indonesia, which combines technological innovation with strong Islamic finance principles to achieve broader and sustainable financial inclusion.